Diseño del Plan Operativo para la gestión ambiental caso parque Santa Clara de Sangolquí - Heredia Dávila, Daniel Fernando (2007)
Designing the Operational Plan for Environmental Management, with which the best mechanisms for proper applicability of the legal basis in this field is established and the character of conservation is fostered by society in a participatory manner towards the environment and promotes sustainable development between them.